CLINICAL EFFICACY OF PROLONGED LOW-DOSE CLARITHROMYCIN THERAPY IN CHRONIC RHINOSINUSITIS WITH NASAL POLYPS (International journal of medical sciences, 2026)
Chronic rhinosinusitis with nasal polyps (CRSwNP) is a debilitating inflammatory condition characterized by a high recurrence rate despite standard medical and surgical interventions. Macrolide antibiotics, beyond their antimicrobial properties, exhibit potent immunomodulatory and anti-inflammatory effects. This article presents a prospective clinical study conducted at the Department of Otorhinolaryngology of Andijan State Medical Institute. Using the IMRAD framework, the research evaluates the clinical and endoscopic efficacy of a prolonged, twelve-week course of low-dose clarithromycin as an add-on therapy for patients with refractory CRSwNP. The study involved ninety adult patients, assessing outcomes through the Sino-Nasal Outcome Test (SNOT-22) and Lund-Kennedy endoscopic scores. The results demonstrate that patients receiving low-dose clarithromycin experienced a statistically significant reduction in polyp size, mucosal edema, and purulent discharge, alongside profound improvements in subjective quality of life compared to the placebo control group. The study concludes that prolonged low-dose macrolide therapy serves as a highly effective and safe conservative treatment modality, potentially reducing the need for repeated surgical interventions in patients with chronic polypoid sinonasal disease.